The Influence of Price Perceptions on the Decision to Use Maxim's Online Transportation Services - Ismi Alvia Damayanti; Indah Nihayatur Romadhoniah; Zidny Nabiel Hussein; Zulfa Fahmy; Khairani Zikrinawati (Experimental Student Experiences, 2024)
Consumer decision making when buying or using a product or service cannot be considered the same, it could be because of the price perception according to the consumer himself. This study aims to determine the effect of price perceptions on how much it influences the decision to use Maxim's online transportation service. Data collection techniques were carried out by distributing questionnaires. The data used in this research is primary data. This study used a non-probability sampling method and an accidental sampling method with a total sample of 103 respondents. The results of the research based on simple linear regression analysis show that the price perception variable has a positive effect on user decisions. From the calculation results, the consistent value of the user's decision variable is 2,951 and the value of the price perception regression coefficient is 0,71. The regression coefficient is positive so that it can be said that the direction of the influence of the X and Y variables is positive. In this case the ability of the independent variable, namely price perception, has an influence of 77.5% while the remaining 22.5% is influenced by other factors not examined in this study.